Combined Effect of Proprioceptive Neuromuscular Facilitation And Electrical Muscle Stimulation In Hemiplegic Stroke Patients To Enhance Upper Extremity Function: A Research Protocol - Palak P. Darda; Divya Jethwani; Moh’d Irshad Qureshi; Ragini Dadgal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background- : Stoke is characterized as rapid clinical signs of focal (or global) impairment of brainfunction, with symptoms that last longer than one day or lead to death, with no other apparent cause thanvascular origin. Globally, Cerebrovascular(CVE)damage is the second-biggest root cause of death and thethird-largest cause of disability. This is 1 in 19 deaths. Stroke is a significant source of injury in the longterm and is more disabled than fatal. This protocol has been created that describes the design of experimentalstudy to evaluate the combined effect of Neuromuscular Electrical Stimulation(NMES) with ProprioceptiveNeuromuscular Facilitation(PNF) to enhance the upper- extremity functions in hemiplegic stroke patients.Methods-The participants (n=26) will be recruited in the study suffering from stroke and meeting theinclusion criteria. Two groups will be formed such that patients in group A will be treated with conventionaltherapy and PNF group B will be treated with PNF and NMES in alongwith conventional therapy. Theprotocol will cover 6 weeks of treatment. Regular assessment at 0,3rdand 6th week will be carried out.In the rehabilitation period, we will evaluate upper extremity function, activities of daily living(ADLs),mental status examination at regular interval during the rehab.Our outcome measures will be- Glasgowcoma scale (GCS), Mini-Mental Scale Examination (MMSE), Modified Ashworth Scale (MAS), ModifiedBarthelIndex(MBI) and Action Research Arm Test(ARAT).Discussion-Efficacy of the intervention will be evaluated by analyzing the upper extremity function usingAction Research Arm Test (ARAT) and level of disability by using Modified Barthel Index Scale. The resultof the study will significantly provide affirmation on using combination therapy of PNF with NMES instroke patients